Systematicity Over the Course of Early Development: An Analysis of Phonological Networks - Laing, Catherine E. (Language and speech, 2025)
This paper explores the early lexicons of nine infants acquiring English or French to determine the extent of systematicity in the early vocabulary, and how this changes over time. Network graphs are generated from the point of first word production in the dataset until age 30 months. Two measures of systematicity—mean path length and clustering coefficient—are analyzed to establish the extent to which the early productive lexicon consists of closely connected clusters of similar-sounding forms. Results show that early production is highly systematic when compared with random networks, but that the network becomes more dispersed as it increases in size. Connectivity within the network is consistently higher for infants’ actual productions when compared with the adult target forms, and this effect increases over time. This suggests a systematic approach to production over the course of early development.